2007
DOI: 10.1002/gps.1760
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of behavioral and psychological symptoms in early‐onset and late‐onset Alzheimer's disease

Abstract: In EO-AD, behavioral and psychological symptoms are relatively fewer than LO-AD at the first medical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 35 publications
9
69
2
3
Order By: Relevance
“…Results from studies assessing the prevalence rates of NPS in outpatient samples applying the NPI are summarized in table 2 (9,(17)(18)(19)(20)(21)(22)(23)(24)(25). Four studies (9,17,23,24) presented the proportion of patients who experienced at least one NPI symptom (> 0), which ranged from 88% to 98%.…”
Section: Nps In Persons With Dementia Attending Outpatient Clinicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from studies assessing the prevalence rates of NPS in outpatient samples applying the NPI are summarized in table 2 (9,(17)(18)(19)(20)(21)(22)(23)(24)(25). Four studies (9,17,23,24) presented the proportion of patients who experienced at least one NPI symptom (> 0), which ranged from 88% to 98%.…”
Section: Nps In Persons With Dementia Attending Outpatient Clinicsmentioning
confidence: 99%
“…The study of Aalten et al, in which one of the inclusion criteria was having at least one clinically significant (> 3) NPI symptom, pooled several datasets, and some of the participants in other studies noted in the table may have been included in this study (18). Toyota et al compared patients with early-onset dementia to patients with late-onset dementia and found that delusions, hallucinations, agitation/aggression, disinhibition, and aberrant motor behavior were more common in lateonset dementia (19). Longitudinal studies indicate that virtually all persons with dementia experienced NPS during the follow-up.…”
Section: Nps In Persons With Dementia Attending Outpatient Clinicsmentioning
confidence: 99%
“…For instance, Toyota et al (2007) compared NPS between community-dwelling people with YO-AD and LO-AD and did not find differences regarding the prevalence of depressive symptoms and anxiety. Moreover, they found fewer delusions and hallucinations as well as less agitation, disinhibition, and aberrant motor behavior in YO-AD than in LO-AD.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies did not find any distinctive differences between EOAD and LOAD patients (Cummings et al, 1985;Bayles et al, 1987;Grady et al, 1987;Selnes et al, 1988;Toyota et al, 2007) or have attributed such differences to dementia severity (Jacobs et al, 1994;Smits et al, 2012). Regarding memory, a relative sparing of memory in EOAD has been reported (Binetti et al, 1996;Smits et al, 2012), while several studies have found that LOAD patients present primarily with memory difficulties (Jacobs et al, 1994;Imamura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%